The Development of Islamic Securities Crowdfunding in Indonesia: Opportunities and Challenges - Aldino Akbar Ibrahimmovic; Muhammad Ichsan maulana Zanri; Muhammad Jihad Ramadhani; Muhammad Andreansyah (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
The rapid advancement of financial technology has transformed Indonesia's financing landscape through the emergence of Islamic securities crowdfunding as a Shariah-compliant alternative financing instrument. This study aims to analyze the development of Islamic securities crowdfunding in Indonesia by examining its opportunities and challenges within the contexts of economic development, accounting, and global financial markets. The study adopts a qualitative, non-empirical design using a library research approach. Data were obtained from peer-reviewed publications, official reports issued by the Financial Services Authority (OJK), and Shariah regulations promulgated by the National Sharia Council–Indonesian Ulema Council (DSN-MUI), which were analyzed through qualitative content analysis and thematic interpretation. The findings indicate that Islamic securities crowdfunding expands financing access for micro, small, and medium enterprises while promoting financial inclusion and Shariah-compliant investment through digital platforms. Regulatory support has strengthened institutional governance and enhanced investor confidence, although challenges remain, including limited Islamic financial literacy, investment risk, regulatory adaptation, Shariah governance, and technological readiness. The study concludes that Islamic securities crowdfunding possesses significant potential to strengthen Indonesia's Islamic digital financial ecosystem, provided that governance quality, stakeholder collaboration, public literacy, and regulatory effectiveness continue to improve.